1933
DOI: 10.1063/1.1749225
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Specific Heats: III. Molecular Rotation in Crystalline Primary Normal Amyl Ammonium Chloride

Abstract: The heat capacity of primary normal amyl ammonium chloride was measu red between 20° and 280°K. If the substance is quenched to 90°K a metastable form is obtained which upon heat ing above 165°K slowly changes toward an apparently st able form. Two regions of gradual transition were found. X-ray powder diffraction photographs taken above and below the transition regions were remarkably similar. The experimental results are interpreted on the basis of rotation of the NH3C5H11+ groups in the crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1933
1933
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Transition enthalpies determined on the warming runs of the DSC measurement for the sample cooled by three different methods are shown in Table 1 together with the reported data of the heat capacity studied by Southard et al, (9) as well as those of DSC by Tsau and Gilson (1). The heat anomaly observed at 238 K on warming the sample in the DTA measurements could not be observed in our DSC experiments.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Transition enthalpies determined on the warming runs of the DSC measurement for the sample cooled by three different methods are shown in Table 1 together with the reported data of the heat capacity studied by Southard et al, (9) as well as those of DSC by Tsau and Gilson (1). The heat anomaly observed at 238 K on warming the sample in the DTA measurements could not be observed in our DSC experiments.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that, when the sample was rapidly cooled to 90 K, a metastable phase was obtained and was slowly transformed on heating into a stable phase above 165 K. Consequently, they concluded that the transition observed at 222 K is that between the metastable and stable phases. On the other hand, Tsau and Gilson (1) determined by Southard et al (9). Furthermore, the transition enthalpy measured by DSC turned out to be several times larger than those of the old study (9).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations